Differences in Increasing The Ability of Reasoning in Problem Based Learning Model and Computer-Based Group Investigation - Syafrizal, Agus; Syahputra, Edi; Irvan, Irvan (Malikussaleh Journal of Mathematics Learning (MJML), 2020)
This study was conducted to determine whether there were significant differences between students 'reasoning abilities taught using the PBL model and with the Computer Multimedia Assisted GI, and to determine whether or not there was an influence of interaction between learning models and students' initial abilities on mathematical reasoning abilities . This research is a comparative research with treatment. The population in this study were students of MTs Al-Washliyah 28 Sergai. The variables in this study are mathematical reasoning abilities by collecting data using a questionnaire and tests of mathematical reasoning abilities as well as student achievement tests. The analysis prerequisite test uses the Kolmogorov-Smirnov normality test with a sig (2-tailed) value for the Computer Multimedia Assisted PBL class is 0.200*>0.005 and the sig (2-tailed) value for the computer multimedia-assisted GI class is 0.132>0.005. Hypothesis testing uses 2 path analysis of variance (Anova) with SPSS aids. The results showed that there were significant differences between students' reasoning abilities taught with the PBL and with the Computer Multimedia Assisted GI with a sig value of 0,000<0.05. And there is no effect of interaction between learning models and students' initial abilities on students reasoning abilities with a sig value of 0.175>0.05.